Comparing Jupiter interior structure models to Juno gravity measurements and the role of a dilute core - Wahl, S. M.; Hubbard, W. B.; Militzer, B.; Guillot, T.; Miguel, Y.; Movshovitz, N.; Kaspi, Y.; Helled, R.; Reese, D.; Galanti, E.; Levin, S.; Connerney, J. E.; et al. (Geophysical research letters, 2017)
The Juno spacecraft has measured Jupiter's low‐order, even gravitational moments, J2–J8, to an unprecedented precision, providing important constraints on the density profile and core mass of the planet. Here we report on a selection of interior models based on ab initio computer simulations of hydrogen‐helium mixtures. We demonstrate that a dilute core, expanded to a significant fraction of the planet's radius, is helpful in reconciling the calculated Jn with Juno's observations. Although model predictions are strongly affected by the chosen equation of state, the prediction of an enrichment of Z in the deep, metallic envelope over that in the shallow, molecular envelope holds. We estimate Jupiter's core to contain a 7–25 Earth mass of heavy elements. We discuss the current difficulties in reconciling measured Jn with the equations of state and with theory for formation and evolution of the planet. Plain Language Summary The Juno spacecraft has measured Jupiter's gravity to unprecedented precision. We present models of the planet's interior structure, which treat the hydrogen‐helium mixture using computer simulations of the material. We demonstrate that dilute core, with the heavy elements dissolved in hydrogen and expanded outward through a portion of the planet, may be helpful for explaining Juno's measurements.